AKAR DAN BUAH TEGALSARI: DINAMIKA SANTRI DAN KETURUNAN KIAI PESANTREN TEGALSARI PONOROGO - Dawam Multazam (Mozaic : Islam Nusantara, 2018)
Pesantren Tegalsari Ponorogo that was born in the early 18th century is considered to have an important role in the history of Islam in Nusantara. This Pesantren is even believed as the first boarding institution and was born in 1742. This article examines historically the forerunner and the early development of Pesantren Tegalsari. Then, the role of students and descendants of kiai. By using the method of historical research and data mining to written documents, interviews, and observations, it is concluded that Pesantren Tegalsari has a close relationship with the elite in the past such as the Wali Songo and the King of Majapahit. In addition, through the students and descendants of kiai, these schools also have a major role in society, both in the propagation of Islam as well as in politics.